The Pimaricin in the treatment of trichomoniasis. Some experiences with pimafucin - Barrionuevo de Vílchez, Tula (2015)
One of the three symptoms of vaginal discharge is ginecopatías and vaginal leucorrhea of origin or vaginitis, comprises a considerable number of patients in gynecological practice.